EVOLUTION OF MODERN PHARMACY: BETWEEN ARTISANAL COMPOUNDING AND TECHNOLOGICAL INNOVATION (CIPEEX, 2025)
Modern pharmacy is the result of a continuous process of evolution, in which the artisanal tradition of compounding merges with technological innovation. This study, based on a literature review of various articles and historical documents, analyzed aspects such as the comparison between compounded and industrialized medicines, the emergence of “gourmet” formulations, the digitalization of pharmacies, and the historical trajectory of the pharmaceutical profession in Brazil. The findings show that compounded and industrialized medicines are complementary, as they offer both personalization and large-scale standardized production. “Gourmet” formulations emerge as an innovative strategy to improve therapeutic adherence, especially among children and the elderly. Digitalization and the use of technologies, such as computerized systems and robotics, demonstrate significant advances in reducing errors and expanding access to services, though they require continuous investment. The history of pharmacy in Brazil reveals the transition from old apothecaries to industrialization and the reinvention of the pharmacist’s role, who today is increasingly engaged in pharmaceutical care and technological management. It is concluded that contemporary pharmacy is sustained by three main pillars: personalization, technological modernization, and historical evolution. Its future depends on the ability to integrate these dimensions while maintaining technical quality and close interaction with patients.